Penerapan Model Pembelajaran Berbasis Masalah Terintegrasi Media Internet Pada Pembelajaran Kimia Larutan Untuk Meningkatkan Hasil Belajar dan Karakter Siswa SMA - Susilo Sudarman; Ramlan Silaban (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. This study aims to determine: 1). The learning outcomes differences between students who learned with an integrated model of Problem Based Learning (PBL) Internet media and Internet media integrated Direct Instruction (DI) and Direct Instruction (DI) learning. 2) The difference of character values of tolerance, communicative, confidence, respect democratic achievements and spreading among the students who learned with an integrated model of PBL and the Internet media DI teaching model integrated Internet media as well as the DI teaching model. 3) There is an interaction between the characters tolerant, communicative, confidence, appreciate spreading democratic achievements and the learning outcomes of students who learned with an integrated model of PBL and the Internet media DI teaching model integrated Internet media as well as the DI teaching model. 4) what cognitive domains spreading the students who learned with an integrated model of PBL and the Internet media DI teaching model integrated Internet media as well as the DI teaching model. The sample in this study consisted of three experimental class. Before the first treatment that has been done in the pre-test validation by a team of experts. Student learning outcomes measured by achievement test instrument using the normalized gain, while for the characters used questionnaires and observation. The analysis technique used Anacova significant at α 0,0. The hypothesis was tested using univariate general linear models. The results showed that there were significant differences in learning outcomes of students who received learning PBL model with an integrated internet and integrated Internet Direct Instruction and Direct Instruction Model .2. There are differences in character values of tolerance, communicative, confident, achievement and respect democratic spreading among the students who learned with an integrated model of PBL Internet and DI model of integrated Internet and DI. Keywords: problem based learning, direct instruction, media internet